2018
DOI: 10.1080/15592294.2018.1469892
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide methylomic and transcriptomic analyses identify subtype-specific epigenetic signatures commonly dysregulated in glioma stem cells and glioblastoma

Abstract: Glioma stem cells (GSCs), a subpopulation of tumor cells, contribute to tumor heterogeneity and therapy resistance. Gene expression profiling classified glioblastoma (GBM) and GSCs into four transcriptomically-defined subtypes. Here, we determined the DNA methylation signatures in transcriptomically pre-classified GSC and GBM bulk tumors subtypes. We hypothesized that these DNA methylation signatures correlate with gene expression and are uniquely associated either with only GSCs or only GBM bulk tumors. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…7 Additional studies have focused on mutation profiles and methylation status. 8 Here we expand the characterization of GSCs by focusing on RNA-mediated mechanisms. Splicing profiles of MES and PN GSC lines show major differences affecting genes implicated in cell cycle regulation, DNA repair, cilium assembly, and RNA splicing.…”
Section: Introductionmentioning
confidence: 99%
“…7 Additional studies have focused on mutation profiles and methylation status. 8 Here we expand the characterization of GSCs by focusing on RNA-mediated mechanisms. Splicing profiles of MES and PN GSC lines show major differences affecting genes implicated in cell cycle regulation, DNA repair, cilium assembly, and RNA splicing.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the earlier studies used a candidate gene approach focused on selected genes; other important genes may have been missed. In recent years, a number of powerful technologies have emerged that allow high‐throughput detection of genome‐wide epigenetic changes in diseases, and especially, the bead array technology developed by Illumina could now provide genome‐wide methylation status at single‐nucleotide resolution . However, these studies mainly were conducted in European or American populations; only a few samples from Asian populations were included .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of powerful technologies have emerged that allow high-throughput detection of genome-wide epigenetic changes in diseases, [13][14][15] and especially, the bead array technology developed by Illumina could now provide genome-wide methylation status at single-nucleotide resolution. [16][17][18][19] However, these studies mainly were conducted in European or American populations; only a few samples from Asian populations were included. 20,21 In European and American populations, the occurrence of HCC is mostly related to alcoholic hepatitis, while in Asian populations, the pathogenesis of HCC is mainly associated with hepatitis B virus or hepatitis C virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…Multiparametric integrative analyses of chromatin immunoprecipitationsequencing (ChIP-seq) on multiple histone modifications, RNA-sequencing (RNA-seq) and DNA methylation now define epigenomic landscapes for subtypes of cancers, which can predict their relative aggressiveness and survival, and highlight potential targets for future treatment approaches [16,17]. It has been shown that the methylome profiles correlate well with such comprehensive molecular portraits [14,[16][17][18] even at the level of knowledge achievable with a rather selective method of microarray-based methylome analysis. The authors of the studies involving epigenomic subtyping of the tumors emphasize that their results not only suggest that DNA methylation plays critical roles in tumorigenesis but may potentially be proposed as a diagnostic biomarker for prognostication and clinical stratification of patients, and making therapeutic decisions [14,18,19].…”
mentioning
confidence: 99%
“…It has been shown that the methylome profiles correlate well with such comprehensive molecular portraits [14,[16][17][18] even at the level of knowledge achievable with a rather selective method of microarray-based methylome analysis. The authors of the studies involving epigenomic subtyping of the tumors emphasize that their results not only suggest that DNA methylation plays critical roles in tumorigenesis but may potentially be proposed as a diagnostic biomarker for prognostication and clinical stratification of patients, and making therapeutic decisions [14,18,19]. We suggest that a more purposeful approach such as genome-wide bisulfite sequencing of the CpG islands, the regions thought to be most important for the regulation of genes expression by DNA methylation, is destined to provide even more copious and reliable methylome profiling with high biological relevance [20].…”
mentioning
confidence: 99%